Association between intimate partner violence and posttraumatic stress disorder: a case-control study - Contreras Pezzotti, Leddy Marina (2010)
Background: Intimate partner violence (IPV) against women is a common form of interpersonal violence in both developed and developing countries, and represents a forensic and public health problem. IPV is related to Post-traumatic Stress Disorder (PTSD). This relationship however, has not been investigated in Colombian population. Objective: To determine the strength of the association between IPV and PTSD in women referred for forensic psychiatric evaluation in Bucaramanga, Colombia. Method: A case-control study was designed. A total of 132 cases involving women referred for forensic psychiatric evaluation met criteria for PSTD according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV). A group of 262 women without PTSD were taken as controls. First, odds ratio (OR) was computed. Logistic regression was used to control confounding variables. Results: A total of 76 (56.6%) in the case group reported IPV during the past year compared to 85 (32.6%) in the control group. IPV and PTSD were associated (OR=3.09, 95%CI: 1.58-6.03) after controlling for age, employment, medico-legal loss or injury, and current aggressor (partner). Conclusions: IPV increased the risk for PTSD three-fold among women attending forensic assessment in Bucaramanga, Colombia.